(untitled) (Journal of Educational Management, 2012)
This paper presents the findings of a study into transitional challenges facing polytechnic management’" in Ghana, effects of those challenges on the quality delivery of polytechnic education and how polytechnic management was managing such challenges. The research was a descriptive survey involving 340 respondents drawn from 6 polytechnics in Ghana. Respondents included both senior members and senior staff. Data were gathered through questionnaire and interviews. Informed by the study, the paper argues that the management of polytechnics encounter a number of challenges. some of which are easily manageable whilst others require strategic management skills to address. It further advocates a stronger collaboration between the polytechnics and industry as a way of promoting quality competency-based training in the country.